Effect of Land Use and Land Cover Changes on Land Degradation in Upper Turkwel Watershed - Toromo, A. K.; Ucakuwun, E. K.; Kipkorir, E. C. (Africa Environmental Review Journal, 2020)
Land use and Land Cover Changes continue in Turkwel watershed owing to climate changes and anthropogenic activities and has led to land degradation. Due to the increasing population in watersheds and growing unplanned human settlement with cultivation extending into ecologically fragile areas, others with relatively good agricultural potential, there is a need to manage the changes taking place. The study examined the land use and land cover changes that have taken place in the Upper Turkwel watershed in the period 1987 to 2017 and its effect on land degradation. The research used spatial land use supervised classification approaches to examine trend changes in land use in the Watershed to understand the changes taking place in the watershed and how it is affecting sustainable development of the watershed and in particular Turkwel dam reservoir. The research finding established six dominant land uses namely forest, farmland, shrubland, grassland, bare land, and water and that forest cover, farmland, and shrub land were on the decline in the watershed with a reduction of 73 km2, 116 km2, and 14 km2, respectively and this led to more land degradation dynamics across the watershed.